Facile synthesis of novel halogenated 4-pyrazolylspirocyclic-β-lactams: versatile heterocyclic synthons. Issue 25 (22nd June 2016) - Bhalla, Aman; Bari, Shamsher S.; Bhalla, Jitender; Khullar, Sadhika; Mandal, Sanjay
Graphical abstract: A mild approach for the synthesis of halogenated 4-pyrazolylspirocyclic-β-lactams via halogen (I2, Br2, ICl) mediated intrasulfenyl cyclisation of cis -3-(prop-2′-ynyloxy)-4-pyrazolyl-β-lactams is described. The behaviour of the substrate towards the nature and variable amount of halogen was investigated. The structural and stereochemical analysis of novel β-lactams were carried out using FT-IR, NMR ( 1 H and 13 C), 2D-NMR (COSY and HSQC), elemental analysis (CHNS), mass spectrometry (EIMS) and single crystal X-ray crystallographic studies (3a, 6a, 7a ). NMR experiments were also performed on cis -3-chloro-4-pyrazolyl-β-lactams to establish the relationship between isomeric ratio of rotamers and nature of solvents. The cis or trans configuration of the hydrogen/chloro/nucleophile substituent at C-3 was assigned with respect to C4-H. Highlights: Exploration of cyclisation, electrophilic addition and electophilic substituttion in mild synthesis. Facile synthesis of halogenated 4-pyrazolylspirocyclic-β-lactams via halogen mediated intrasulfenyl cyclisation. Comparative studies with halogenating agents for attaining stereoselectivity and variety. Stereochemistry at C3 of 3-propargyloxy-β-lactams 3a was established by X-ray structural analysis. 4-Pyrazolylspirocyclic-β-lactams 6a & 7a were established by X-ray crystallographic studies. NMR experiments were performed to confirm conformational isomerism shown by 4-pyrazolyl-β-lactams. Abstract: A mild approach for the synthesis of halogenated 4-pyrazolylspirocyclic-β-lactams via halogen (I2, Br2, ICl) mediated intrasulfenyl cyclisation of cis -3-(prop-2′-ynyloxy)-4-pyrazolyl-β-lactams is described. The behaviour of the substrate towards the nature and variable amount of halogen was investigated. The structural and stereochemical analysis of novel β-lactams were carried out using FT-IR, NMR ( 1 H and 13 C), 2D-NMR (COSY and HSQC), elemental analysis (CHNS), mass spectrometry (EIMS) and single crystal X-ray crystallographic studies (3a, 6a, 7a ). NMR experiments were also performed on cis -3-chloro-4-pyrazolyl-β-lactams to establish the relationship between isomeric ratio of rotamers and nature of solvents. The cis or trans configuration of the hydrogen/chloro/nucleophile substituent at C-3 was assigned with respect to C4-H.